Analysis of Arab-Islamic Cultural Integration in Arabic Language Teaching Materials Based on Book Iḍāʾāt Li Mu'allimi Al-Lughah Al-ʿarabīyah Li Ghayr Al-Nāṭiqīn Bihā - Dewi, Dita Puspita; Yuliani, Sri Yulia; Ramadhani, Gita Putri; Abdurahman, Maman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the principles of Arab-Islamic cultural integration in Arabic teaching materials based on Chapter 2 of the Book of Iḍāʾāt li Mu’allimi al-Lughah al-ʿArabīyah li Ghayr al-Nāṭiqīn Bihā by Abdur Rahman (2010). The approach used is qualitative descriptive with a targeted content analysis method that focuses on identifying relevant cultural elements in teaching Arabic to non-Arabic speakers. The results of the study show that the integration of Arab-Islamic culture is an essential component in the preparation of Arabic teaching materials, including aspects of formal language (al-fuṣḥā), Islamic values, social habits of the Arab community, and the use of cultural-based supporting media. The study reveals that Arabic teaching materials must transcend linguistic instruction to embrace Arab-Islamic cultural narratives, balancing these with local Indonesian contexts to avoid dissonance and enhance relevance. Practical recommendations advocate for intercultural and Content and Language Integrated Learning (CLIL) approaches leveraging religious texts and culturally rich media while adhering to the Common European Framework of Reference (CEFR). Evaluation through the CIPP model (Context, Input, Process, Product) is emphasized to ensure alignment with educational goals and cultural sensitivities. This research contributes a framework for developing Arabic teaching materials that harmonize linguistic mastery, Islamic values, and local cultural identity, fostering students’ communicative competence and intercultural empathy in Indonesia’s diverse Islamic educational landscape.